A job-seeking competency model for North Korean defectors who are college students in South Korea. Issue 1 (2nd January 2019) - Yoon, Hyung Joon; Ahn, Sungsik; Kang, Eun Hee
ABSTRACT: The purpose of this study was to develop a job-seeking competency model for North Korean defectors (NKDs) who are college students in South Korea. This study adopted the Delphi method with a panel of 17 experts, comprising of NKDs who secured their jobs successfully and South Korean field experts who have hired NKDs or assisted them with their employment. Through three Delphi rounds, 18 job-seeking competencies were identified with the definition, behavioural indicators, and competency significance. In addition, the preliminary utility of the competency model was examined. Implications of the study results and future directions for enhancing the validity and utility of the competency model are discussed.